Climate Resilience Plan for the National Bean Chain in Honduras 2021 - 2024 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
This plan, developed participatory consultations in 6 departments, provides clear guidelines to address short and medium-term challenges caused by climate changes in the production and marketing of beans in Honduras.